Food safety in Latin American informal food establishments - Pariza, Teodora; Cho, Min Jung (Frontiers in Sustainability, 2024)
Background and aim Informal food establishments are an important source of food due to their increased affordability of products and convenience. Food security and safety are two key factors that must coexist for a proper functioning of the food system. In Latin America, the safety of food is less analyzed than food security, although it is central to people’s health, as well as to their personal sustainability. Since informal food establishments are popular food sources in Latin America, this research aims to examine the presence of foodborne pathogens in food products from such establishments. Methods This research will be conducted as narrative literature review, collecting data from all publications in Spanish-speaking countries in Latin America between January 1, 2018, and May 31, 2023. The databases searched were PubMed and Web of Science. The search included pathogens such as bacteria, parasites and viruses. The languages of the articles assessed were English and Spanish. Results The analysis was based on 32 articles focusing on seven of all Spanish-speaking countries in Latin America. The pathogens found belonged either to a bacteria type, or to a parasite. No viruses were investigated within the selection of articles. The widest variety of pathogens was among bacteria. The most frequently identified bacteria belonged to the family Enterobacteriaceae. The food products examined ranged from animal products to fruit and vegetables, fish, seafood and already-prepared dishes or juices. The informal food establishments where the studies conducted their analyses were markets, backyard selling points, street establishments or convenience food stores. Conclusion Identifying pathogens in food products commercialized at different informal retail points has impacts for the safety of the food from personal sustainability viewpoint. Therefore, efforts need to be directed toward better support of the informal food sector in their provision of safe food. Further investigation could trace the exact sources of infection, while public health officials can implement safety programs in cooperation with food vendors.